ALTERNATIVE DISPUTE RESOLUTION MECHANISMS AND INTERNAL DEMOCRACY IN NIGERIA - Omoyeni Tolulope Julius; Falusi Fisayo Samuel; Onuoha Anthony Uchenna (International Studies Journal)
The internal democracy of political parties is a vital component of democratic societies, as it ensures the fairness and transparency of political processes. However, internal conflicts and disputes often arise within political parties, leading to an increasing number of pre-election court cases in Nigeria. These court cases have become a burden on the judiciary, given the limited number of courts and judges available to handle them. Recently, the President of the Court of Appeal publicly lamented the volume more than 600 appeals of pre-election court cases relating to the conduct of political parties' primary elections, which reportedly placed significant stress on the judiciary. It was even reported on February 27, 2023 that a judge died in his office while preparing to attend a court session. To end, this study explores the use of alternative dispute resolution mechanisms in enhancing internal democracy in Nigerian political parties. Using a qualitative research approach, this study analyzes the various alternative dispute resolution mechanisms commonly employed by Nigerian political parties, including mediation, arbitration, and negotiation. The study also examines case studies of successful and unsuccessful use of alternative dispute resolution mechanisms in Nigerian political parties. The findings indicate that while alternative dispute resolution mechanisms have the potential to enhance internal democracy in Nigerian political parties, their effectiveness is often hindered by factors such as inadequate legal frameworks, godfatherism, excessive power exacted by political office holders especially governors in their state and lack of political will from party leaders. The study concludes with that though political parties do involve in Mediation and negotiation, the third aspect of ADR has not fully been explore which is Arbitration within political party setup. This study thus recommends enhancement in use of alternative dispute resolution mechanisms in Nigerian political parties, including the need for legal reforms for arbitration, Education and workshops for political parties and the promotion of a culture of dialogue and compromise within political parties to reduce the burden on the judiciary and enhance internal democracy. Therefore the study seeks to contribute to the ongoing discussions on how to strengthen internal democracy in Nigerian political parties and reduce the burden on the judiciary.